IMPLEMENTATION ANALYSIS EXTRACURRICULAR ACTIVITIES POLICY IN SUPPORTING THE VISION AND MISSION OF EDUCATION AT AL-ISHLAH BONDOWOSO PLUS ELEMENTARY SCHOOL - Sugiharto, Achmad Bagus (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2023)
The school's vision, mission, goals and quality assurance are part of the school's inputs in the school organization system. The vision, mission, goals and quality assurance are manifested by actualizing school programs in the form of school activities. The process of organizing school activities is divided into three, namely: (a) intracurricular activities, (b) co-curricular activities, and (c) extracurricular activities. To support the implementation of intracurricular activities, co-curricular and extracurricular activities, schools have educational program policies. These policies are then implemented in order to make the school output in accordance with the vision, mission, goals and quality assurance of the school. In addition to the concept of education, this research framework will also refer to the concepts of policy analysis studies. Policy analysis studies are studies that direct their studies on several aspects of policy, including the policy-making process, policy implementation and policy evaluation. The entire policy implementation analysis approach is directed at analyzing the achievement of the vision and mission of education in the educational institution that is the subject of the research.